Analyzing Gender Equality Indicators Using Principal Component Analysis in Central Papua and Papua Highland - Shafira Renianti, Fayza; Suliyanto; Amelia, Dita; Mardianto, M. Fariz Fadillah; Ana, Elly (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The Gender equality is one of the key targets in Sustainable Development Goal (SDG) 5 and remains a major challenge in Central Papua and Papua Highland, where gender development indicators are among the lowest in Indonesia. This study aims to identify the dominant factors influencing gender equality in these two provinces using Principal Component Analysis (PCA) on seven indicators representing education, health, economic conditions, and political representation of women. The analysis results show that two main factors are formed with a total variance explained of 77.248%. The first factor reflects women’s economic participation and basic living conditions, while the second factor represents resource capacity and socio-political representation. These findings suggest that limited access to education, health services, and participation in the labor market and political institutions are the primary contributors to gender inequality in this region. Therefore, empowerment-oriented policies and improved service accessibility are required to achieve more equitable gender development in Papua.